Age-Specific Estimates of Respiratory Syncytial Virus-Associated Hospitalizations in 6 European Countries: A Time Series Analysis. (24th June 2022) - Johannesen, Caroline K; van Wijhe, Maarten; Tong, Sabine; Fernández, Liliana V; Heikkinen, Terho; van Boven, Michiel; Wang, Xin; Bøås, Håkon; Li, You; Campbell, Harry; Paget, John; Stona, Luca; et al.
Abstract: Background: Knowledge on age-specific hospitalizations associated with RSV infection is limited due to limited testing, especially in older children and adults in whom RSV infections are not expected to be severe. Burden estimates based on RSV coding of hospital admissions are known to underestimate the burden of RSV. We aimed to provide robust and reliable age-specific burden estimates of RSV-associated hospital admissions based on data on respiratory infections from national health registers and laboratory-confirmed cases of RSV. Methods: We conducted multiseason regression analysis of weekly hospitalizations with respiratory infection and weekly laboratory-confirmed cases of RSV and influenza as covariates, based on national health registers and laboratory databases across 6 European countries. The burden of RSV-associated hospitalizations was estimated by age group, clinical diagnosis, and presence of underlying medical conditions. Results: Across the 6 European countries, hospitalizations of children with respiratory infections were clearly associated with RSV, with associated proportions ranging from 28% to 60% in children younger than 3 months and we found substantial proportions of admissions to hospital with respiratory infections associated with RSV in children younger than 3 years. Associated proportions were highest among hospitalizations with ICD-10 codes of "bronchitis and bronchiolitis." In all 6 countries, annual incidence of RSV-associated hospitalizations was >40 per 1000 persons in the age group 0–2 months. In age group 1–2 years the incidence rate ranged from 1.3 to 10.5 hospitalizations per 1000. Adults older than 85 years had hospitalizations with respiratory infection associated to RSV in all 6 countries although incidence rates were low. Conclusions: Our findings highlight the substantial proportion of RSV infections among hospital admissions across different ages and may help public health professionals and policy makers when planning prevention and control strategies. In addition, our findings provide valuable insights for health care professionals attending to both children and adults presenting with symptoms of viral respiratory infections.